Educational management with a focus on balanced scorecard performance indicators - Barra, Geraldo Magela Jardim (2021)
The aim of this study is to propose a maturity model for educational management of higher education institutions focusing on the balanced scorecard - BSC. Based on the Evaluation Instrument of the National Higher Education Evaluation System - Sinaes - and the BSC, the educational management roadmap was built. This roadmap was evaluated by a group of experts. It was verified that this model presented a strategic map that can act as an instrument for guiding efforts for better performance results of teaching units. The teaching unit's mission will be translated into a set of performance measures that will underpin a strategic measurement and management system. In the Roadmap, performance will be measured within four balanced perspectives: People, Processes, Positioning, and Performance, which, through a set of objectives and goals, the performance vectors articulate into a cause and effect relationship. The roadmap can be used to prescribe strategic actions in educational units so that they can evolve from a certain level of maturity to a higher level, configuring a process of continuous administrative and academic improvement.